CONCEPTS AND APPROACHES IN ISLAMIC STUDIES - Herdifa Pratama (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2022)
The study of Islam is one form of study that has received attention among scholar, not only at the national level but also as a discourse for world scholars. This study of Islam is then known as Islamic studies. If explored in depth, it appears that Islamic studies have begun to be widely studies by enthusiasts of relihious studies and other studies. Thus, Islamic studies deserve to be used as a branch of scientific discipline. This means that Islamic studies have a place in the world of science. This is the urgency to discuss the concepts and approaches used in Islamic studies.. This research is a library research on literatures that have relevance to the object of the problem. Through the descriptive-qualitative method, this study found that study of Islam places Islam in three dimensions, namely Islam as a source of teachings, Islam as thought, and Islam as practice. In order to examine the three dimensions of Islam, a scientific and faith-based approach is needed which will result in the study of Islam as a scientific discipline and the study of Islam based on belief and faith.